Mixing the virtual and real worlds in ready-to-wear shopping using the magic mirror (Journal of the College of Basic Education, 2022)
Abstract In the midst of the acceleration of international companies in searching for the best devices and inventions of modern technology, including sensors and three-dimensional scanner, which relies entirely on algorithms .All these innovations have a real and positive impact in the future of the world of fashion to compete in the marketing of ready-made clothes away from the classic methods In the design, manufacture and marketing of garments . From this point , the current research highlights the importance of modern technology that simulates the body and combines imagination and reality with the virtual mirror system (Magic Mirror), which allows shoppers in clothing retail stores to try it in the store (virtually) on the magic mirror . This mirror reduces the usage of fitting room in addition to provide space, it also allows the consumer to choose clothing from a range of choices and experience on the avatar. This research includes the first research problem, the importance of research, research objectives and terminology. The second topic, which included the theoretical framework of the concept of virtual simulation in the system of magic mirror as well as identify the components of the magical women system and its benefits. The third section included the results of the research and conclusions and recommendations.